Implementation of Jarimatika Method to Improve Multiplication Calculation Ability in Grade III Elementary School Students - Akrom, Muhamad; Zihab, Zihab; Jalaluddin, Jalaluddin; Imam Muslim, Rachmat (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2024)
This study aims to describe the use of the jarimatika method to improve multiplication calculation skills in grade III students at SD Negeri 2 Surabaya Utara in the 2023/2024 Academic Year. This research approach is a classroom action research with four stages, namely planning, implementation, observation, and reflection. Data collection techniques in this study used observation, tests and documentation. The data obtained from the research results were then analyzed using data analysis consisting of three stages, namely (1) data reduction, (2) data presentation, (3) drawing conclusions. Based on the initial conditions, the first data obtained were only 11 students (60.4%) whose scores were able to reach the KKTP while 14 students (39.6%) whose scores were below the KKTP. After conducting the research, the results obtained showed that in cycle I there were 19 students (72.48) who were able to achieve the KKTP score and 6 (27.52%) students whose scores were below the KKTP. Meanwhile, in cycle II, there were 2 students (19.28) who were below the KKTP and 23 (80.72%) students who were able to achieve the KKTP score. This shows that learning activities using the jarimatika method can improve student learning outcomes in multiplication material.